2002
DOI: 10.1111/j.1365-2621.2002.tb11391.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Supercritical Fluid Extraction of Natural Vitamin E from Wheat Germ Using Response Surface Methodology

Abstract: Natural vitamin E was extracted by supercritical fluid extraction of carbon dioxide (SFE-CO 2 ) from wheat germ. Several SFE-CO 2 parameters, such as extracting pressure, extracting temperature, and flow rate of carbon dioxide were examined as the independent variables of central composite rotate design (CCRD). Through the response surface methodology (RSM), the optimal processing conditions were determined and the quadratic response surfaces were drawn from the mathematical models. The results demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 8 publications
2
36
0
1
Order By: Relevance
“…This was done by writing the second-order regression equation in matrix form as described by Montgomery (2001b) and Ge et al (2002). The point thus obtained is known as the stationary point, X 1S , X 2S , X 3S (X 1S = 337 bar, X 2S = 70°C and X 3S = 1.78 h).…”
Section: Optimal Processing Conditionsmentioning
confidence: 99%
“…This was done by writing the second-order regression equation in matrix form as described by Montgomery (2001b) and Ge et al (2002). The point thus obtained is known as the stationary point, X 1S , X 2S , X 3S (X 1S = 337 bar, X 2S = 70°C and X 3S = 1.78 h).…”
Section: Optimal Processing Conditionsmentioning
confidence: 99%
“…The wheat germ is characterized also by a palatable taste due to its high oil and sugar contents. Although plant proteins are generally considered of low biological value; the protein isolate from defatted wheat germ meal has been recognized as highly nutritional and utilized for some food products (Ge et al, 2002). The wheat germ proteins were reported to consist of 34.5% albumin as the major fraction followed by globulins (15%), gluten (10.6%) and prolamine (4.6%) and to have a very well balanced amino acids make-up being quite similar to that of egg proteins as indicated by Zhu et al (2006).…”
Section: Int J Dairymentioning
confidence: 99%
“…Consequently, when we fitted a response surface model to tocopherol extraction yield (the product Y oil C toc ), we obtained an equation that was qualitatively similar to Equation (5), indicating that the tocopherol extraction yield depended highly on the oil extraction yield because of the small changes in tocopherol content in the oil as a function of extraction conditions (results not shown). To the best of our knowledge, there is no information on the effect of SC-CO 2 extraction conditions on the yield of rapeseed tocopherols, but Ge et al (2002) reported that the tocopherol yield from wheat germ increased with system pressure.…”
Section: Concentration Of Tocopherolsmentioning
confidence: 99%